Cambridge Servicemen’s Memorial (Breuer, 1945): a public space for remembrance - Salvador José Sanchís Gisbert; Pedro Ponce Gregorio; Ignacio Peris Blat (VLC Arquitectura)
Marcel Breuer was in the first year of architectural technicians to graduate from Bauhaus School. The peculiar education he received there allowed him to explore the concept of design in its broadest sense. In his European stage we find, on the most private and small scale, unique solutions for furniture. In his first American stage we see a strong commitment with solutions related to the residential land and, when he earned international recognition, he developed large scale solutions for his public non-residential buildings and urban equipments in locations all over the world. It is strange to see that an architect like him did not have the opportunity to materialize any of his proposals associated with the public space. The 1945 Cambridge Servicemen’s Memorial project, also known as the Memorial War, is the most significant one he developed in his last years in Cambridge. Had it been built, it would have been a valuable example of modernity and contemporary reinterpretation of the monument in the public space.